GENDER PROBLEMS OF TECHNICAL EDUCATION - ROUČOVÁ, Eva (Trends in education, 2008)
The presented thesis provides a theoretical view of gender analysis a student's concept of technical curriculum in the subject didactics of studying of primary school teaching.
Keywords: technical education; student of teaching; gender problems